Description of ovary organization and oogenesis in a phreodrilid clitellate. (29th November 2019) - Świątek, Piotr; Pinder, Adrian; Gajda, Łukasz
Abstract: Phreodrilidae is a small family uniting about 50 species of minute freshwater clitellate annelids inhabiting mainly the Southern hemisphere. Other than the male and spermathecal genitalia, their internal organization is poorly known. Here, we present results of our study of the ovaries and oogenesis in Insulodrilus bifidus, a phreodrilid from Western Australia using light and electron microscopy. The ovaries are paired and located in segment XII. They are inconspicuous and composed of several (10–12) spherical germ‐line cysts loosely interconnected by flattened somatic cells. The cysts usually comprise 32 germ cells and each cell is connected via a cytoplasmic bridge (ring canal) to the central cytoplasmic mass (the cytophore). In ovaries, germ cells in a given cyst develop in full synchrony. However, there is no synchrony among cysts, so there is a developmental gradient of cysts (from oogonial to early meiotic) along the longitudinal ovary axis. Within the cysts that are located in the distal end of the ovary the synchrony is finally lost and interconnected cells diversify into two morphologically distinct categories: an oocyte and 31 nurse cells. Such cysts detach from the ovaries and further development occurs within the body cavity. The oocyte gathers nutrients, mainly in form of yolk spheres, whereas nurse cells grow slightly and do not gather yolk. Organelles such as ribosomes, mitochondria and endoplasmic reticulum pass freely through the ring canals and are present within the cytophore, which suggests cytoplasmic transfer towards the oocyte. The formation of female germ‐line cysts equipped with cytophore and cells differentiated into oocyte and nurse cells matches the general pattern of oogenesis found in clitellates. In details, the ovary organization and oogenesis found in I. bifidus resembles the situation described in some representatives of Naidinae and Enchytraeidae. Abstract : Scheme presents the ovary organization and oogenesis in the phreodrilid studied. Ovaries (A) are composed of several gem‐line cyst (arrows) witch quickly detach and float in the body cavity (B‐D). Each cyst is composed from 32 cells and anuclear cytoplasmic mass, the cytophore (cy). Germ cells differentiate into one oocyte (o) and 31 nurse cells (nc). Only oocyte finalizes oogenesis. E and F show 3D reconstructions of germ line cysts based on serial semi‐thin sections. Oocyte is in red, nurse cell nuclei are in blue.